Saturday

January 31, 2015

January 31, 2015

Posted by **Liz** on Monday, November 30, 2009 at 12:24am.

- Algebra -
**drwls**, Monday, November 30, 2009 at 6:48amThe standard quadratic equation form is

ax^2 + bx + c = 0

and your equation is, if your (2) is supposed to be an exponent,

12x^2 -15x = 0

Therefore a = 12, b = -15 and c = 0

You have reduced your equaion to

4x^2 -5x = 0,

so using a=4, b=-5 and c=0 would give you the same results for x.

You should get x = 0 and x = 5/4 as the solutions, using the quadratic equation

x = [-b +/-sqrt(b^2 -4ac)]/(2a)

**Answer this Question**

**Related Questions**

Algebra - -0.2x+12x+11 solve by using quadratic equation

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

Algebra - Solve the quadratic equation. 3x^2-15x+18=0 I know that the formula to...

Algebra 2 - Factor each quadratic equation: 8x^2+10x-3 25x^2+10x-3 9x^2-15x-14 ...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

College Algebra - Solve the following equation in the complex number system x^4+...

help...solving a polynomial....algebra - solve this please....help me....12x(...

Alegbra 2 - PLEASE HELP!!!!!!!!!!!!!!!!!! Solve each equation using the ...

Algebra - To solve 9x^2-12x+4=49 by using the Square Root Property, you would ...

math - solve the equation x^3-5x^2-4x+20=0 I need a hint on how to solve this ...